The proposed affiliation of Arbor Vitae and helping hand - Donnelly, Anne Cohn; Shaw, Kathy ([London] : SAGE, 2016)
This case examines the merger of two nonprofit organizations from the point of view of the board of directors and senior staff leaders.
Originally Published in: Donnelly, A., & Shaw, K. (2009). The Proposed Affiliation of Arbor Vitae and Helping Hand. 5-408-756. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Case studies; Non-governmental organizations -- Management -- Case studies